The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/cdev.12919
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Theory of Mind in a Small‐Scale Society: A Case Study From Vanuatu

Abstract: Although theory of mind (ToM) is argued to emerge between 3 and 5 years of age, data from non-Western, small-scale societies suggest diversity. Deeper investigations into these settings are warranted. In the current study, over 400 Melanesian children from Vanuatu (range = 3-14 years), growing up in either urban or rural remote environments, completed culturally tailored ToM batteries. Results show a marked delay in false belief (FB) performance, particularly among participants from rural villages. By further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 63 publications
4
46
0
1
Order By: Relevance
“…The same progression difference was found for Iranian children (Shahaeian et al 2011), and a completely novel one in Vanuatu (Dixson et al 2017). In fact, Dixson et al (2017) established great differences in the sequence between different social groups within one culture, suggesting that even relatively small differences 2 A disambiguation of the terms folk psychology and theory of mind is due here. Folk psychology is a common-sense conceptual framework (a theory) that people in a given culture explicitly deploy when explaining, predicting, or manipulating the behavior of other people and higher animals (Churchland 1998, p. 3).…”
Section: Current Empirical Datasupporting
confidence: 61%
See 2 more Smart Citations
“…The same progression difference was found for Iranian children (Shahaeian et al 2011), and a completely novel one in Vanuatu (Dixson et al 2017). In fact, Dixson et al (2017) established great differences in the sequence between different social groups within one culture, suggesting that even relatively small differences 2 A disambiguation of the terms folk psychology and theory of mind is due here. Folk psychology is a common-sense conceptual framework (a theory) that people in a given culture explicitly deploy when explaining, predicting, or manipulating the behavior of other people and higher animals (Churchland 1998, p. 3).…”
Section: Current Empirical Datasupporting
confidence: 61%
“…Chinese and American children take different trajectories in ToM scale progression (ToM scale is a set of tests designed by Wellman et al for more fine-grained measurement of ToM than the single FBT can provide) (Wellman et al 2011). The same progression difference was found for Iranian children (Shahaeian et al 2011), and a completely novel one in Vanuatu (Dixson et al 2017). In fact, Dixson et al (2017) established great differences in the sequence between different social groups within one culture, suggesting that even relatively small differences 2 A disambiguation of the terms folk psychology and theory of mind is due here.…”
Section: Current Empirical Datamentioning
confidence: 80%
See 1 more Smart Citation
“…In the Pacific, children master the false belief task at an older age than their Western counterparts (Wassman, Träuble & Funke 2013). Those same Pacific children, however, find it easier than Western children to understand hidden emotions (the man doesn't like the gift, but does not want to show his disappointment) (Dixson, Komugabe‐Dixson, Dixson & Low 2018; see also Harris & Tang 2018).…”
Section: Towards An Anthropology Of Mindmentioning
confidence: 99%
“…Opacity beliefs do seem to have an impact on how people in these societies reason about minds. Developmental research has found that in societies with Opacity of Mind, children pass the false belief task at older ages than non-Opacity countries (Callaghan et al, 2005;Dixson, Komugabe-Dixson, Dixson, & Low, 2017;Knight et al, 2004;Mayer & Trauble, 2012). These beliefs also impact moral reasoning.…”
Section: Cultural Differences In Conceiving Of and Reasoning About Mindsmentioning
confidence: 99%